Put it as a decimal
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We start with our original expression: 1 0 ( 2 1 + 5 1 + 1 0 1 ) − 1 . First, we sum the fractions inside the parentheses, which gives us 5 4 . Substituting this into our expression, we get: 1 0 ( 5 4 ) − 1 . Notice that x − n = x n 1 . From this, we can say that ( 5 4 ) − 1 = 5 4 1 1 = 5 4 1 = 4 5 . Substituting this into our expression, we get: 1 0 ( 4 5 ) . Simplifying this, we get: 4 1 0 ⋅ 5 = 4 5 0 = 2 2 5 = 1 2 . 5 .